Pengembangan Catur SPLDV untuk Membantu Siswa dalam Menyelesaikan Sistem Persamaan Linier Dua Variabel - Arie Wibowo (Pusat Pengembangan dan Pemberdayaan Pendidik dan Tenaga Kependidikan Matematika, 2019)
Learning mathematics aims to make students able to solve problems they will face in the future. This can be hampered if students have difficulty in learning. Difficulties experienced by students in solving system of linear equations material, namely difficulties to carry out procedures in determining the completion. In learning, the teacher has not used teaching aids to overcome student difficulties. Teaching aids can be an alternative solution to determine the completion of system of linear equations. This study aims to produce teaching aids that can help students to determine the solution. The type of research applied was a 4D model development research. To produce good teaching aids, valid tests, practical tests and effective tests were carried out. In this study, the produced teaching aid is called “Catur SPLDV”. The validity test result of the teaching aid was 3.59 with very valid criteria. The practicaliy test result of Catur SPLDV was 86.67%; very practical criteria. While the effective test result is 0.73 with high criteria analyzed using the normalized-gain (n-gain) test. Catur SPLDV is used to help students to determine the solution of linear equations system of two-variable using the concept of Cartesian coordinates and number patterns. It can be used while playing a game, and containing a little algebraic elements making it easier for students to determine the solution of system of linear equations with two-variable.